2008
DOI: 10.1002/ejsp.542
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes of singles: are singles what we think?

Abstract: Four studies examined the accuracy of the single stereotype by comparing perceptions of single and partnered targets with self-ratings and ratings by others of single and partnered participants. Results revealed that single targets were evaluated more negatively than partnered targets in terms of a wide range of personality characteristics, overall well-being, and satisfaction with relationships status. These findings were very robust and not qualified by target sex, participant sex, and participant relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
2
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(129 citation statements)
references
References 48 publications
7
103
2
17
Order By: Relevance
“…While people in committed relationships are often perceived favorably, people who are single are negatively stereotyped as lonelier and less mature, secure, and happy (Morris, DePaulo, Hertel, & Taylor, 2008). Despite little evidence of their veracity (Greitemeyer, 2009), these stereotypes appear to be widely accepted, applied to male and female singles who are as young as 25 years old (Morris et al, 2008) and even to singles who demonstrate social skills by maintaining close friendships (Conley & Collins, 2002).…”
Section: List Of Figuresmentioning
confidence: 99%
“…While people in committed relationships are often perceived favorably, people who are single are negatively stereotyped as lonelier and less mature, secure, and happy (Morris, DePaulo, Hertel, & Taylor, 2008). Despite little evidence of their veracity (Greitemeyer, 2009), these stereotypes appear to be widely accepted, applied to male and female singles who are as young as 25 years old (Morris et al, 2008) and even to singles who demonstrate social skills by maintaining close friendships (Conley & Collins, 2002).…”
Section: List Of Figuresmentioning
confidence: 99%
“…6,11 Hypotheses concerning specific differences should not be based on the current discourse for the simple fact that these are likely to have been derived from stereotypes, which are often inaccurate when compared to selfreport measures. 12,13 Any subsequent hypotheses concerning markers of smartphone ownership should instead be considered in the context of brand personality.…”
mentioning
confidence: 99%
“…For instance, single and married mothers have similar personality characteristics, overall psychological well-being, and are similarly vulnerable and reactive to stressors (Avison, Ali, & Walters, 2007;Greitemeyer, 2009). Kendig and Bianchi (2008) found that single mothers do not spend significantly less time with their children than do married mothers.…”
mentioning
confidence: 99%